2015
DOI: 10.1038/srep13842
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction of Apolipoprotein-E isoforms with insulin receptors modulates brain insulin signaling in mutant human amyloid precursor protein transgenic mice

Abstract: It is unclear how human apolipoprotein E4 (ApoE4) increases the risk for Alzheimer’s disease (AD). Although Aβ levels can lead to insulin signaling impairment, these experiments were done in the absence of human ApoE. To examine ApoE role, we crossed the human ApoE-targeted replacement mice with mutant human amyloid precursor protein (APP) mice. In 26 week old mice with lower Aβ levels, the expression and phosphorylation of insulin signaling proteins remained comparable among APP, ApoE3xAPP and ApoE4xAPP mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…It was reported that the disturbance of insulin signaling was worse in amyloid model mice expressing human apoE4 (ApoE4/APP) which correlates with poorer memory performance, compared with ApoE3/APP mice (Chan et al, 2015; Chan et al, 2016). However, it is still unclear whether Aβ and apoE4 play synergistic or competing roles in disrupting insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the disturbance of insulin signaling was worse in amyloid model mice expressing human apoE4 (ApoE4/APP) which correlates with poorer memory performance, compared with ApoE3/APP mice (Chan et al, 2015; Chan et al, 2016). However, it is still unclear whether Aβ and apoE4 play synergistic or competing roles in disrupting insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether Aβ and apoE4 play synergistic or competing roles in disrupting insulin signaling. It was shown that in the presence of Aβ, apoE4 bound more to Aβ whereas apoE3 bound more to IR (Chan et al, 2015). Our current findings demonstrate that apoE4 has higher binding affinity to IR in the absence of Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…Ong et al [64] reported a reduction of Akt phosphorylation at Thr308 at 32 weeks and at Ser473 at 72 weeks of age in apoE4-TR mice as compared to apoE3-TR mice. Chan et al [93] reported that in 26-week old mice, there was no difference in the expression and phosphorylation of insulin signaling proteins among APP, APOE3xAPP, and APOE4xAPP mouse brains while when the mice aged to 78 weeks, these proteins were markedly reduced in APP and APOE4xAPP mouse brains.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between amyloid β and insulin resistance is also modulated by ApoE genotype [47]. The interplay between amyloid β, insulin, and ApoE isoforms were investigated using an APP mouse model expressing human ApoE isoforms [48,49]. ApoE4 enhanced the amyloid β-induced impairment of insulin signaling and accelerated the hippocampal-dependent cognitive deficits, as compared with ApoE3 [49].…”
Section: Apolipoprotein E In Metabolism Of Lipid and Glucosementioning
confidence: 99%
“…ApoE4 enhanced the amyloid β-induced impairment of insulin signaling and accelerated the hippocampal-dependent cognitive deficits, as compared with ApoE3 [49]. There was less insulin receptor coimmunoprecipitated with ApoE in brain lysates of APP/ApoE4 mice as compared with that in APP/ApoE3 mice, suggesting a weaker interaction between insulin receptor and ApoE4 as compared with ApoE3 [48]. Because amyloid plaque burden is higher in the ApoE4 mice compared with ApoE3 mice, it is hard to rule out whether the higher amount of amyloid β in the APP/ApoE4 mice actually contributes to the insulin resistance.…”
Section: Apolipoprotein E In Metabolism Of Lipid and Glucosementioning
confidence: 99%